Lectotypification of Callicarpa integerrima (Lamiaceae) - Ma, Zhonghui; Huang, Rongshao; Su, Zhiwei (Phytotaxa, 2015)
The genus Callicarpa Linnaeus (1753: 111) with about 140 species is mainly distributed in temperate, subtropical and tropical Asia, America, Australia and the Pacific Islands (Harley et al. 2004; Bramley 2013; Zhang 2014; Ma & Su 2015), with 48 species and 13 varieties occurring in China (Chen & Gilbert 1994). Callicarpa was long thought to be included in Verbenaceae. However, based on morphological and molecular phylogenetic studies on the Verbenaceae and Lamiaceae, Callicarpa was transferred to Lamiaceae, along with Viticoideae and several other genera (Bramley 2009, 2013; Ma et al. 2015). During a taxonimic study of this genus in China, the name C. integerrima Champion ex Bentham (1853: 135) tourned out not yet typified. C. integerrima is currently accepted as endemic species of China (Chen & Gilbert 1994) and was described based on plants collected in Hongkong (Bentham 1853), but no specimens were cited in the protologue. We traced in K two duplicate specimens (K barcodes K000674744 and K000674745) collected by J.G. Champion in Hongkong that fit the protologue and can be regarded as syntypes (Art. 9.5 of the ICN, McNeill et al. 2012). The specimen K barcode K000674744 is better preserved and complete (flowers and fruits), and is selected here as the lectotype.